A Short Media History of English Literature - Berensmeyer, Ingo (De Gruyter, 2022)
This book explores the history of literature as a history of changing media and modes of communication, from manuscript to print, from the codex to the computer, and from paper to digital platforms. It argues that literature has evolved, and continues to evolve, in sync with material forms and formats that engage our senses in multiple ways. Because literary experiences are embedded in, and enabled by, media, the book focuses on literature as a changing combination of material and immaterial features. The principal agents of this history are no longer genres, authors, and texts but configurations of media and technologies. In telling the story of these combinations from prehistory to the present, Ingo Berensmeyer distinguishes between three successive dominants of media usage that have shaped literary history: performance, representation, and connection. Using English literature as a test case for a long view of media history, this book combines an unusual bird's eye view across periods with illuminating readings of key texts. It will prove an invaluable resource for teaching and for independent study in English or comparative literature and media studies.